Design and Analysis of Low-Speed External Frame Motors with Halbach-Type and Olive-Shaped Magnet Structures - Rana Md Sohel; Youtao Shen; Runze Ji; Kai Liu (World Electric Vehicle Journal, 2025)
This study examined the design and optimization of low-speed external frame motors featuring Halbach-type and olive-shaped magnet structures to improve performance in spacecraft control moment gyroscopes (CMGs). Our research was driven by the urgent need for precise, high-torque, low-speed motors in CMGs, where conventional designs, including Halbach-type and traditional radial magnet configurations, are hindered by manufacturing complexity and excessive torque pulsation. This study focused on optimizing rotor pole configurations to enhance efficiency and torque stability. An olive-shaped magnet structure provides a more uniform magnetic field distribution in the air gap, substantially reducing magnetic field harmonics and minimizing cogging torque and torque pulsation—critical performance factors for low-speed applications. Comparative analysis reveals that the olive-shaped motor achieves a peak torque of 0.312 N·m with a torque pulsation of 0.9 mN·m, maintaining an amplitude below 0.3%. This demonstrates a 20% improvement compared to the Halbach-type motor’s torque pulsation of 1.15 mN·m. Moreover, the olive-shaped motor exhibits superior stability in air-gap magnetization under different loads, ensuring high efficiency and robust operation. By streamlining magnet assembly while enhancing electromagnetic performance, this study offers a cost-effective, high-precision solution for CMG systems. These findings underscore the olive-shaped magnet motor’s potential to advance motor technology for aerospace applications.